Estimating intra‐seasonal intrinsic water‐use efficiency from high‐resolution tree‐ring δ13C data in boreal Scots pine forests - Tang, Yu; Sahlstedt, Elina; Young, Giles; Schiestl‐Aalto, Pauliina; Saurer, Matthias; Kolari, Pasi; Jyske, Tuula; Bäck, Jaana; Rinne‐Garmston, Katja T. (Wiley, 2022)
Intrinsic water-use efficiency (iWUE), a key index for carbon and water balance, has been widely estimated from tree-ring δ13C at annual resolution, but rarely at high-resolution intraseasonal scale. We estimated high-resolution iWUE from laser-ablation δ13C analysis of tree-rings (iWUEiso) and compared it with iWUE derived from gas exchange (iWUEgas) and eddy covariance (iWUEEC) data for two Pinus sylvestris forests from 2002 to 2019. By carefully timing iWUEiso via modeled tree-ring growth, iWUEiso aligned well with iWUEgas and iWUEEC at intraseasonal scale. However, year-to-year patterns of iWUEgas, iWUEiso, and iWUEEC were different, possibly due to distinct environmental drivers on iWUE across leaf, tree, and ecosystem scales. We quantified the modification of iWUEiso by postphotosynthetic δ13C enrichment from leaf sucrose to tree rings and by nonexplicit inclusion of mesophyll and photorespiration terms in photosynthetic discrimination model, which resulted in overestimation of iWUEiso by up to 11% and 14%, respectively. We thus extended the application of tree-ring δ13C for iWUE estimates to high-resolution intraseasonal scale. The comparison of iWUEgas, iWUEiso, and iWUEEC provides important insights into physiological acclimation of trees across leaf, tree, and ecosystem scales under climate change and improves the upscaling of ecological models.
Keywords: eddy covariance (EC); intrins ic water-use efficiency (iWUE); laser ablation; leaf gas exchange; mesophyll conductance; Pinus sylvestris L.; post-photosynthetic isotopic fractionation; tree-ring δ13C